2014
DOI: 10.3892/mmr.2014.2382
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin synergized with cyclosporine A improves cardiac allograft survival by suppressing inflammation and apoptosis

Abstract: Melatonin, a widespread physiological mediator, has been demonstrated to exhibit a dose‑dependent immunoregulatory effect in vitro and in vivo, including mediating physiological circadian rhythms, neutralizing free radicals and exerting antisenescence actions. In the present study, the efficacy and mechanism of melatonin alone or in combination with cyclosporine (CsA) in prolonging heart transplantation survival was examined. Daily treatment with melatonin (200 mg/kg/day) through a gavage, significantly prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Most scholars believe that this disease is an autoimmune inflammation reaction caused predominantly by genetic factors, in addition to being stimulated by trauma, infection, fatigue and other environmental factors (25)(26)(27). The present results showed that naringin attenuates NF-κB p65 unit, TNF-α, IL-1β and IL-6 activity in AS mice.…”
Section: A B a Bsupporting
confidence: 57%
“…Most scholars believe that this disease is an autoimmune inflammation reaction caused predominantly by genetic factors, in addition to being stimulated by trauma, infection, fatigue and other environmental factors (25)(26)(27). The present results showed that naringin attenuates NF-κB p65 unit, TNF-α, IL-1β and IL-6 activity in AS mice.…”
Section: A B a Bsupporting
confidence: 57%
“…Study results showed significantly reduced lymphocyte proliferative capacity, abrogated acute allograft rejection and prolonged graft survival in animals who were treated with a high dose of MLT. These results were reproduced by Liu et al [ 53 ], who found that MLT improved graft survival and also alleviated the inflammatory response and apoptosis in cardiac tissue after HTx.…”
Section: Comprehensive Reviewsupporting
confidence: 69%
“…Melatonin also produced beneficial effects in cardiac transplantation through a synergetic action with CsA in a rat model (Liu et al 2014). The authors administered 200 mg/kg/day of melatonin to one group, 20 mg/kg/day of CsA to the second group, and 50 mg/kg/day of melatonin with 5 mg/kg/day of CsA to the third group.…”
Section: Cardiac Transplantationmentioning
confidence: 99%